Improved cotton yield: Can we achieve this goal by regulating the coordination of source and sink? - Qin, Aizhi; Aluko, Oluwaseun Olayemi; Liu, Zhixin; Yang, Jincheng; Hu, Mengke; Guan, Liping; Sun, Xuwu (Frontiers in Plant Science, 2023)
Cotton is one of the major cash crops globally. It is characterized by determinate growth and multiple fruiting, which makes the source–sink contradiction more obvious. Coordination between source and sink is crucial for normal growth, yield, and quality of cotton. Numerous studies reported how the assimilate transport and distribution under varying environmental cues affected crop yields. However, less is known about the functional mechanism underlying the assimilate transport between source and sink, and how their distribution impacts cotton growth. Here, we provided an overview of the assimilate transport and distribution mechanisms , and discussed the regulatory mechanisms involved in source-sink balance in relation to cotton yield. Therefore, this review enriched our knowledge of the regulatory mechanism involved in source–sink relationship for improved cotton yield.